VD_FINDINFO Arrêt / 2024 / 907 vom 21. Oktober 2024 - VD Tribunal cantonal (2024)
ADMISSION DE LA DEMANDE, MOYEN AUXILIAIRE, CHAUSSURES ORTHOPÉDIQUES | 21 LAI, 8 al. 1 LAI, 8 al. 2 LAI, 51 LPGA, 53 al. 1 LPGA, 53 al. 2 LPGA, 61 let. c LPGA, 2 al. 1 OMAI, 4.01 Annexe OMAI, 14 RAI